2014
DOI: 10.1007/s10450-014-9618-8
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and desulfurization activities of metal oxide/biomass-based activated carbons prepared by blending method

Abstract: Column activated carbons were prepared from walnut shell chars and transition metal oxide powders (i.e. Co 2 O 3 , Ni 2 O 3 , CuO and V 2 O 5 ) with blending method. Samples were characterized by N 2 adsorption-desorption, X-ray diffraction, X-ray photoelectron spectroscopy and Fourier-transform infrared spectroscopy. The texture properties of all modified activated carbons with metal oxides dosage of \5 wt% did not change evidently. The basic functionalities of these activated carbons increased relative to bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Some metal oxides were detected in the XPS spectra, such as FeO, CoO, CuO and NiO, while XRD results only showed metallic particles on most modied activated coke. 12 As a result, the metals on activated coke had a lower valence state in this study since metal oxides had a stronger reduction atmosphere during activation process than calcination, possibly resulting from using the steam as activation agent. The scanning depth of XPS method is about 3 nm generally, while the XRD has a deeper scanning depth.…”
Section: Metal Phase On Activated Coke Before Desulphurizationmentioning
confidence: 85%
See 3 more Smart Citations
“…Some metal oxides were detected in the XPS spectra, such as FeO, CoO, CuO and NiO, while XRD results only showed metallic particles on most modied activated coke. 12 As a result, the metals on activated coke had a lower valence state in this study since metal oxides had a stronger reduction atmosphere during activation process than calcination, possibly resulting from using the steam as activation agent. The scanning depth of XPS method is about 3 nm generally, while the XRD has a deeper scanning depth.…”
Section: Metal Phase On Activated Coke Before Desulphurizationmentioning
confidence: 85%
“…12 Gao et al 11 investigated the metals modied activated carbon by impregnation method. Some metal oxides were detected in the XPS spectra, such as FeO, CoO, CuO and NiO, while XRD results only showed metallic particles on most modied activated coke.…”
Section: Metal Phase On Activated Coke Before Desulphurizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies showed that the textural properties of pyrolusite modified activated coke change, because the added pyrolusite could react with the carbon substrate during the activation process . High ratio of pyrolusite could introduce excessive metal particles, which might promote the aggregation and the formation of large crystals on activated coke, resulting in the blockage of pores . Thus, an appropriate pyrolusite ratio in activated coke could help to develop good textural properties, which is beneficial for the improvement of its iodine value.…”
Section: Resultsmentioning
confidence: 99%